ANALISIS KUALITATIF PEMANFAATAN KOMPUTER DALAM PROSES PEMBELAJARAN ANAK USIA DINI (Studi Kasus di PAUD Fatiatul Ilmi Kecamatan Tanjungsiang Kabupaten Subang Tahun Pelajaran 2015/2016) - Wulanda Aditya Azis (Tunas Siliwangi, 2016)
This research is motivated by the modern era of globalization, the development of technology productsdevelop very quickly. But in reality introduce computer information technology was introduced only at the primary school level, junior high school or even in high school, but there is no harm if introduced in the scope of early childhood education. The purpose of research is to analyze the planning, implementation, execution and results of the obstacles encountered on the use of such computers in early childhood learning processes on a qualitative analysis of computer use in the process of learning in early childhood Fatiatul Ilmi Tanjungsiang District of Subang district in the academic year 2015/2016. The approach used is a qualitative approach to thematic research techniques of analysis and case study research design. Data collection techniques used were observation, interviews and documentation study. The results of his research on the planning, implementation, execution and results of the obstacles encountered on the use of such computers in early childhood learning processes on a qualitative analysis of computer use in the process of learning in early childhood Fatiatul Ilmi Tanjungsiang District of Subang district in the academic year 2015/2016. This research is expected of teachers in early childhood education is expected to continue to use and develop computer technology in early childhood by learning as possible that can make children more interested and eager to follow it up with a variety of technology-based educational program.Keywords : the use of computers, pembelelajaran early childhood